A dual-mode scheduling approach for task graphs with data parallelism. (2017) - Liu, Yang; Meng, Lin; Taniguchi, Ittetsu; Tomiyama, Hiroyuki
This paper proposes a task scheduling algorithm for multi/many-core systems. To increase the quality of results on the low computational complexity, our algorithm uses two static priorities switched during task scheduling. In our experiments, we compared the proposed algorithm with a state-of-the-art algorithm. The experimental results show that the proposed algorithm yields shorter scheduling length than our previous research.